MOBILITY HABITUS IN THE LITERATUREFROM 2020 TO 2024 - Julio ECrespo (IPHO-Journal of Advance Research in Science And Engineering, 2024)
The objective of the present work is modeling the mobility habitus in the public transport system with low Co2 emission mechanics in the center of Mexico. In this sense, a documentary work was carried out with a review of sources indexed to national repositories, using the Delphi technique for the content analysis and the specification of the model. A study was conducted with a selection of 100 students to establish the reliability,linearity, sphericity, adequation and validity of an instrument from which a relationship of dependence between income and mobility habitus was observed. The limits of the search, selection and processing of information are recognized, and it is recommended to extend the research to international repositories, as well as to employ a more sophisticated technique.